2014
DOI: 10.1097/pas.0000000000000255
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tumor Regression of Esophageal Adenocarcinomas After Neoadjuvant Chemotherapy

Abstract: Histopathologic determination of tumor regression provides important prognostic information for locally advanced gastroesophageal carcinomas after neoadjuvant treatment. Regression grading systems mostly refer to the amount of therapy-induced fibrosis in relation to residual tumor or the estimated percentage of residual tumor in relation to the former tumor site. Although these methods are generally accepted, currently there is no common standard for reporting tumor regression in gastroesophageal cancers. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 25 publications
3
55
0
8
Order By: Relevance
“…The Mandard TRG has subsequently been validated for esophageal adenocarcinoma (41) although several other classifications have been described (42); all, however, remain relatively subjective and are tempered by potential interobserver variability and intratumoral sampling bias (43). Ultimately, the Mandard TRG is most frequently used and provides the basis for optimal prediction of survival (28,30). An additional limitation of this study is its retrospective design over a long time period, which although necessary to generate a sufficient cohort resulted in a change of PET/CT scanner, and the availability of additional metrics for the more recent scanner alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mandard TRG has subsequently been validated for esophageal adenocarcinoma (41) although several other classifications have been described (42); all, however, remain relatively subjective and are tempered by potential interobserver variability and intratumoral sampling bias (43). Ultimately, the Mandard TRG is most frequently used and provides the basis for optimal prediction of survival (28,30). An additional limitation of this study is its retrospective design over a long time period, which although necessary to generate a sufficient cohort resulted in a change of PET/CT scanner, and the availability of additional metrics for the more recent scanner alone.…”
Section: Discussionmentioning
confidence: 99%
“…pTR was defined as Mandard Tumor Regression Grade (TRG) of 3 or less, after dedicated review by a consultant cellular pathologist (27). The Mandard TRG was used in preference to alternative TRGs, being the most frequently used TRG for esophageal cancer (28), with optimal prediction of survival (29,30).…”
Section: Data and Variablesmentioning
confidence: 99%
“…PathCR (i.e., TRG 1) as opposed to any grade of residual carcinoma (i.e., TRGs 2-4) was considered the reference standard. Another commonly made distinction between TRGs 1 and 2 (i.e., 0%-10% residual carcinoma) and TRGs 3 and 4 (i.e., $11% residual carcinoma) was not made, because this distinction is rather arbitrary in terms of interpathologist reproducibility and overall survival (2,4,23), and the potential clinical consequences of such a distinction are unclear.…”
Section: Histopathologic Assessmentmentioning
confidence: 99%
“…Previous studies found intratumoral heterogeneity for allelic loss [96, 97] and gene amplification in breast cancer [98, 99]. Two recent reports described large variations in the mutational spectrum of triple negative breast cancer assessed by high-throughput RNA sequencing and deep re-sequencing of more than 2.400 somatic mutations [8, 9]. These studies applied sequencing in great depth of one single sample per tumor.…”
Section: Resultsmentioning
confidence: 99%